The Revival Of Education In Mosques In Medan City From The Late 20th Century To The Early 21st Century - Muhammad Roshan Ramadhan; Zaini Dahlan (Edusoshum : Journal of Islamic Education and Social Humanities, 2026)
This study aims to analyze the transformation of mosque-based education in Medan City during the period of 1980–2024 by examining the development of educational functions, types of programs, curriculum, and governance at Al-Musabbihin Mosque, Al-Muhajirin Bumi Asri Mosque, and Baiturrahman JIP-1 Mosque. The study uses a qualitative approach with a historical method through the stages of heuristics, source criticism, interpretation, and historiography. Data were obtained through documentation, observation, and semi-structured interviews with mosque management/BKM, religious leaders, community leaders, educators, government officials, as well as participants or the community. The results of the study show that mosque-based education has transformed from basic religious activities, such as learning the Qur’an, religious studies, creed, fiqh, and morals, into more diverse non-formal education.  The educational development program includes religious study groups, child and youth guidance, family education, Islamic studies, guidance for converts, as well as social-religious activities. The curriculum also grows adaptively by including character building, moral strengthening, and social issues according to the needs of the congregation. From a management perspective, educational management has evolved from a simple pattern to a more organized and participatory system through the involvement of the Mosque Management Board, educators, religious leaders, community leaders, youth, and the congregation. This study shows that this transformation is a form of mosque adaptation to social changes and the religious needs of urban communities, while also strengthening the mosque's position as a sustainable, community-based non-formal Islamic education institution.